Preconcentration and separation of copper(II), cadmium(II) and chromium(III) in a syringe filled with 3-aminopropyltriethoxysilane supported on silica gel - Tokman, Nilgun; Akman, Suleyman; Ozcan, Mustafa; Koklu, Unel (Springer Science and Business Media LLC, 2002)
In this study, a syringe was filled with silica gel loaded with 3-aminopropyltriethoxysilane, for the separation and preconcentration of copper, cadmium and chromium prior to their determination by graphite furnace atomic absorption spectrometry (GFAAS) in seawater. For this purpose, a syringe was filled with 0.5 g of modified silica gel and the sample solution was drawn into the syringe and ejected back again. The analyte elements were quantitatively retained at pH 5. Then, the elements sorbed by the silica gel were eluted with 2.0 M of HCl and determined by GFAAS. At optimum conditions, the recovery of Cu, Cd and Cr were 96-98%. Detection limits (3delta) were 6.6, 7.5 and 6.0 micro g L(-1) for Cu, Cd and Cr, respectively. The elements could be concentrated by drawing and discharging several portions of sample successively but eluting only once. Cu, Cd and Cr added to a seawater sample were quantitatively recovered (>95%) in the range of the 95% confidence level. The method proposed in this paper was compared with a column technique. Optimum experimental conditions, reproducibility, precision and recoveries of both techniques are the same, but the syringe technique is much faster, easier and more practical than the column technique. It is a portable system and allows one to make the sorption process in the source of sample. In addition, the risk of contamination is less than in the column technique.
Keywords: Chromium; Chromatography; Propylamines; Spectrophotometry, Atomic; Silica Gel; Equipment Design; Hydrogen-Ion Concentration; Silanes; Silicon Dioxide; Metals, Heavy; Seawater; Water Pollutants; Copper; Cadmium